Revision of Two Spinicaudatan Species from the Cañadón Asfalto Formation (Jurassic), Patagonia Argentina - Monferran, Mateo Daniel (2020)
Re-examination under a scanning electron microscope (SEM) of the type material of the species described by Tasch and Volkheimer (1970) and Vallati (1986) was applied, as well as, new materials collected from different localities of the Las Chacritas Member from Cañadón Asfalto Formation (Argentina). Morphological description and new SEM images of the ornamentation pattern revealed features on carapaces that had not been recognized previously. These species are now referred to the family Eosestheriidae as Carapacestheria taschi (Vallati, 1986) and to the family Fushunograptidae as Wolfestheria patagoniensis (Tasch, in Tasch and Volkheimer, 1970). These records increase our knowledge about the Jurassic faunas from Argentina.